Kevin Lee COVID-19 Journal Entry - Lee, Kevin::::::::: (2021)
Journal entry reflecting Kevin Lee's experience with COVID-19 pandemic. The entry includes an image of San Francisco which is the view from the roof of the building he is staying in.